Hubungan Antara Kepercayaan Diri dan Kemampuan Komunikasi Matematis dengan Hasil Belajar Siswa Kelas V - Nisa, Jaziatun; Tisngati, Urip; Suryatin, Suryatin (PGSD STKIP PGRI Pacitan, 2023)
This study aims to determine: (1) the correlation between self-confidence and student’s learning outcomes; (2) the correlation between mathematical communication skills and student’s learning outcomes; (3) the correlation between self-confidence and mathematical communication skills with student’s learning outcomes. This type of research was quantitative. The population in this study were students of class V SD Negeri Gugus 01 in Kebonagung District for the 2019/2020 academic year. The sample was selected by proportional random sampling technique, amounting to 30 respondents. Data collection was carried out using documentation, questionnaires, and tests. Data analysis used correlation techniques with the help of SPSS 16.0 after testing the prerequisite analysis and hypothesis testing. The results showed that: (1) there was a positive correlation between self-confidence and learning outcomes of grade V SD Negeri Gugus 01, Kebonagung Sub District, Academic Year 2019/2020 (2) there was a positive correlation between mathematical communication skills and the learning outcomes of class V SD Negeri Gugus 01, Kebonagung Sub District, 2019/2020 academic and (3) there was a positive correlation between self-confidence and mathematical communication skills with student learning outcomes.